A Ag2CO3/TFA-catalyzed intramolecular annulation approach to imidazo[1, 2-c][1, 3]oxazin-5-one derivatives. Issue 7 (3rd February 2022) - El Qami, Abdelkarim; Jismy, Badr; Akssira, Mohamed; Jacquemin, Johan; Tikad, Abdellatif; Abarbri, Mohamed
Abstract : A series of 2, 7-disubstituted 3-methylimidazo[1, 2- c ][1, 3]oxazin-5-ones were synthesized in good yields via Ag2 CO3 /TFA-mediated intramolecular annulation of N -Boc-2-alkynyl-4-bromo(alkynyl)-5-methylimidazoles. Abstract : A series of 2, 7-disubstituted 3-methylimidazo[1, 2- c ][1, 3]oxazin-5-ones were synthesized in good yields via Ag2 CO3 /TFA-mediated intramolecular annulation of N -Boc-2-alkynyl-4-bromo(alkynyl)-5-methylimidazoles. This methodology was carried out in the presence of a catalytic amount of silver carbonate and trifluoroacetic acid in dichloroethane at 60 °C. In all experiments, only the six-membered ring product was obtained since the possible five-membered compound was not observed, proving the high regioselectivity of this approach. A complementary computational study was performed in order to rationalize the mechanism of 6- endo-dig heterocycle formation. In addition, 2-bromo-3-methyl-7-phenylimidazo[1, 2- c ][1, 3]oxazin-5-one was used as a building block to synthesize a small library of new 2-substituted imidazo[1, 2- c ][1, 3]oxazin-5-one derivatives through the Suzuki, Sonogashira and Heck cross coupling reactions.